Leader as coach : restoring employee motivation and performance. (A) - Cates, Karen L.; Booth, Brenda Ellington (London : Kellogg School of Management, 2019)
Kiera, a young, enthusiastic sales rep, was recently promoted to manager of a sales team of five. In her first year on the job, she tackled a major revamp of the company's outdated training materials and organized a regional conference for her area, but neither her boss nor corporate seemed to appreciate the work she had been doing. Without support or guidance from her boss, Kiera was confused. What was she supposed to do? Parts A and B of the case present two different perspectives on coaching. Part A contains a narrative from the point of view of the "coachee," Kiera, who was learning how to work with her boss, ultimately with the assistance of an executive coach. This case focuses on coaching as a tool to enhance self-management and relationship management and to improve personal performance.
Originally Published InCates, K. L., & Booth, B. E. (2019). Leader as Coach: Restoring Employee Motivation and Performance (A). 5-418-750(A). Evanston, IL: Kellogg School of Management, Northwestern University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Executive coaching -- Case studies; Employees -- Coaching of -- Case studies; Employee motivation -- Case studies; Sales management -- Case studies